High-density lipoprotein protects normotensive and hypertensive rats against ischemia-reperfusion injury through differential regulation of mTORC1 and mTORC2 signaling - Al-Othman, Reham; Al-Jarallah, Aishah; Babiker, Fawzi (Frontiers in Pharmacology, 2024)
Background: High-density lipoprotein (HDL) protects against myocardial ischemiareperfusion (I/R) injury. Mammalian target of rapamycin complexes 1 and 2 (mTORC1 and mTORC2) play opposing roles in protecting against I/R injury, whereby mTORC1 appears to be detrimental while mTORC2 is protective. However, the role of HDL and mTORC signaling in protecting against I/R in hypertensive rodents is not clearly understood. In this study, we investigated the involvement of mTORC1 and mTORC2 in HDL-mediated protection against myocardial I/R injury in normotensive Wistar Kyoto (WKY) rats and spontaneously hypertensive rats (SHR). Methods: Hearts from WKY and SHR were subjected to I/R injury using a modified Langendorff system. Hemodynamics data were collected, and infarct size was measured. Rapamycin and JR-AB2-011 were used to test the role of mTORC1 and mTORC2, respectively. MK-2206 was used to test the role of Akt in HDL-mediated cardiac protection. The expression levels and the activation states of mediators of mTORC1 and mTORC2 signaling and myocardial apoptosis were measured by immunoblotting and/or enzyme-linked immunosorbent assay (ELISA). Results: HDL protected hearts from WKY and SHR against I/R injury as indicated by significant improvements in cardiac hemodynamics and reduction in infarct size. HDL induced greater protection in WKY compared to SHR. HDL treatment attenuated mTORC1 signaling in WKY by reducing the phosphorylation of P70S6K (mTORC1 substrate). In SHR however, HDL attenuated mTORC1 signaling by reducing the levels of phospho-mTORC1, Rag C (mTORC1 activator), and phospho-PRAS40 (mTORC1 inhibitor). HDL increased the phosphorylation of mTORC2 substrate Akt, specifically the Akt2 isoform in SHR and to a greater extent in WKY. HDL-induced protection was abolished in the presence of Akt antagonist and involved attenuation of GSK, caspase 7, 8 activation, and cytochrome C release. Conclusions: HDL mediates cardiac protection via attenuation of mTORC1, activation of mTORC2-Akt2, and inhibition of myocardial apoptosis. HDL regulates mTORC1 and mTORC2 signaling via distinct mechanisms in normotensive and hypertensive rats. HDL attenuation of mTORC1 and activation of mTORC2-Akt2 signaling could be a mechanism by which HDL protects against myocardial I/R injury in hypertension.